Inflammasome Contribution to the Activation of Th1, Th2, and Th17 Immune Responses - Martynova, Ekaterina; Rizvanov, Albert; Urbanowicz, Richard A.; Khaiboullina, Svetlana (Frontiers in Microbiology, 2022)
Inflammasomes are cytosolic polyprotein complexes formed in response to various external and internal stimuli, including viral and bacterial antigens. The main product of the inflammasome is active caspase 1 which proteolytically cleaves, releasing functional interleukin-1-beta (IL-1β) and interleukin-18 (IL-18). These cytokines play a central role in shaping immune response to pathogens. In this review, we will focus on the mechanisms of inflammasome activation, as well as their role in development of Th1, Th2 and Th17 lymphocytes. The contribution of cytokines IL-1β, IL-18 and IL-33, products of activated inflammasomes, are summarized. Additionally, the role of cytokines released from tissue cells in promoting differentiation of lymphocyte populations are discussed.